Aesthetic Treatment of Lateral Peg-Shaped Incisive with Indirect Veneer Restoration Using Ceramo Polymer Restoration: A Case Report - Patria, Azkya (Indonesia Prosthodontic Association, 2021)
Introduction: Peg shaped is one of the abnormalities of dental anatomy, ie tooth size is smaller than normal, and tapered shape. These peg-shaped teeth are often found in the maxillary lateral incisors and third molars. The shape on the lateral incisor often causes aesthetic problems because of its anterior position. One of the treatments for peg-shaped teeth is Veneer. Case report: 26 years old woman, had a peg-shaped shape on both lateral incisors. Indirect veneer aesthetic treatment was performed using Ceramage to correct the shape and cover the diastema so that better aesthetics would be achieved. Wax-up is done to see the suitability of the shape and proportion of the veneer. The patient can get a visual picture of the expected treatment results. Discussion: The result of the treatment is Ceramage gave a good shape in improving the shape of the Peg-shaped incisor. The color of the veneers also resembles the color of their natural teeth, and the patient is satisfied with the results of the treatment. Ceramage can be used as a treatment option for anterior teeth with deformities. Conclusion: Ceramage veneer is an alternative that can be done to improve the aesthetic appearance at a more economical cost for anterior teeth.